An assessment of the torrefaction of North American pine and life cycle greenhouse gas emissions. (1st April 2016) - McNamee, P.; Adams, P.W.R.; McManus, M.C.; Dooley, B.; Darvell, L.I.; Williams, A.; Jones, J.M.
Highlights: Torrefaction of North American pine improves fuel properties. Comparative LCA is presented of wood pellet and torrefied wood pellet supply. Torrefied pellets offer energy and greenhouse gas savings but increase land use. Torgas use is crucial for emission savings to offset fossil fuel use as utility fuel. Shipping contributes largest emissions and long distance favours torrefied pellets. Abstract: Bioenergy is increasingly being used to meet EU objectives for renewable energy generation and reducing greenhouse gas (GHG) emissions. Problems with using biomass however include high moisture contents, lower calorific value and poor grindability when compared to fossil fuels. Torrefaction is a pre-treatment process that aims to address these issues. In this paper four torrefaction treatments of pine were performed and a mass–energy balance calculated. Using experimental data, a pellet production supply chain incorporating torrefaction was modelled and compared to an existing wood pellet system to determine life-cycle GHG emissions. Two utility fuels, wood chips and natural gas, were considered to provide process heat in addition to volatile gases released during torrefaction (torgas). Experimental results show that torrefaction reduces the moisture content and increases the calorific value of the fuels. Increasing torrefaction temperature and residence time results in lower mass and energy yields. GHG emissions reduce with increasing torrefaction severity. Emissions from drying & torrefaction and shipping are the highest GHG contributors to the supply chain. All 4 torrefaction conditions assessed outperformed traditional wood pellet supply chain emissions but more land is required which increases with temperature and residence time. Sensitivity analysis results show that emissions increase significantly where natural gas is used for utility fuel and no torgas is utilised.